A case of myocardial infarction related to total cystectomy and ileal conduit diversion under general anaesthesia - Izumi, T (Hinyokika kiyo. Acta urologica Japonica, 1984)
Prognosis is extremely poor when an aged patient is attacked by myocardial infarction during or after a major operation. This paper reports that a 63-year-old male patient who had not been specifically diagnosed to have any coronary artery disease before operation recovered from a myocardial infarction which occurred during total cystectomy and ileal conduit diversion under general anesthesia. The continuous electrocardiogram monitoring carried out during general anesthesia enabled us to discover and treat the disease early and save the patient's life. References to the myocardial infarction and the general anesthesia are also discussed